Plasma & Microwaves as Greener Options for Nanodiamond Purification: Insight Into Cytocompatibility - Mitev, Dimitar P.; Alsharabasy, Amir M.; Morrison, Liam; Wittig, Sebastian; Diener, Christof; Pandit, Abhay (Frontiers in Bioengineering and Biotechnology, 2021)
The potential biomedical applications of nanodiamond have been considered over the last few decades. However, there is still uncertainty regarding the extent to which the surface characteristics of this material can influence potential applications. The present study investigated the effects of surface characteristics alongside the prospective of improving nanodiamond production using cold plasma and microwave technologies for the surface tailoring of the nanocarbons. Numerous approaches were applied to purify, refine and modify a group of nanosized diamonds at each step of their production cycle: from the detonation soot as the initial raw material to already certified samples. The degree of surface changes were deliberately performed slowly and kept at different non-diamond carbon presence stages, non-carbon elemental content, and amount converted superficial moieties. In total, 21 treatment procedures and 35 types of nanosize diamond products were investigated. In addition cultures of human fibroblast cells showed enhanced viability in the presence of many of the processed nanodiamonds, indicating the potential for dermal applications of these remarkable nanomaterials.